The relaxed woman : reclaim rest and live an empowered, joy-filled life - Hobbs, Nicola Jane (G.P. Putnam's Sons, 2025)
"We have become a society of rushing women, overburdened women, exhausted women. Women whose lives are plagued with stress, guilt, and burnout. We try so hard to do it all -- to be the perfect partners, mothers, daughters, colleagues, friends -- only to end up feeling not good enough, unappreciated, and lonely. But it doesn't have to be this way. In The Relaxed Woman, psychologist Nicola Jane Hobbs explores how stress negatively impacts our minds, bodies and relationships, and illuminates a path towards reclaiming relaxation as a form of liberation. Weaving together neuroscience and psychology with inspirational stories from women who are discovering the transformational power of rest for themselves, Nicola guides us on a journey to becoming relaxed women: women who have untangled their sense of worth from their productivity, who can rest without guilt and anxiety, who trust their intuitions, honor their needs, and live by their deepest values. Filled with simple rest rituals we can weave into our busy lives, healing practices to help regulate our nervous systems, and practical strategies to support us in navigating the unavoidable stressors of life, The Relaxed Woman is an empowering, restful guide for all of us who long to live more joyful, authentic lives. Because we deserve more than being constantly exhausted. We deserve to be relaxed women, women who know our worth and our powerƯ -- women who, together, can change the world." --